DEGRADASI ZAT WARNA DIREK MERAH SECARA ELEKTROLISIS - Rosigita, Ghatien; Hazlina, Nur; Choirunayli, Nila; Sari, Regina Purwita; Pangastuti, Dini Novita Mayang; Lestari, Sri (Jurusan Kimia FMIPA UNMUL, 2023)
Direct dyes are synthetic dyes of the azo group which can quickly absorb on cellulose fibers and are capable of producing long-lasting quality printing dyes, so they are widely used in the textile industry. However, the waste originating from the dyeing process containing synthetic dyes is difficult to degrade naturally so it will cause environmental pollution. This study aims to degrade red direct dyes by electrolysis using PbO2/Pb electrodes from used batteries. This research was carried out by electrolyzing red direct dye solutions at various work potentials, variations in Na2SO4 concentrations, variations in electrolysis time, and variations in concentrations of red direct dyes. The absorbance of the direct dye solution before and after electrolysis was measured using a UV-VIS spectrophotometer at a wavelength of 550 nm. The results showed that the optimum working potential was 8 volts, the optimum concentration of 0,2 M Na2SO4 and the optimum electrolysis time was 65 minutes. At the optimum working potential, time and concentration of Na2SO4, an increase in the red direct solution concentration will decrease the percentage of decolorization.